213 A STRUCTURED CONTENT ANALYSIS OF THE WEBSITES OF NURSING HOMES WITH RESPECT TO LGBT-INCLUSIVITY. (18th November 2021) - O'Malley, K; Waters, R
Abstract: Background: The challenges associated with ageing can be amplified for individuals who identify as Lesbian Gay Bisexual or Transgender (LGBT). As a cohort, they are more likely to enter long term care at an earlier age than their non-LGBT counterparts. Many LGBT older adults fear negative bias in their interactions with health and social care services, and perceive nursing homes as potentially unwelcoming and insensitive to their needs. Nursing home websites outline the services and facilities available to residents, and can offer an insight into their culture and values. This research sought to examine the LGBT-inclusivity of nursing homes websites in a single catchment area catering to both an urban and rural population. Methods: A total of 41 nursing homes and long term care facilities were identified, of which 24 had websites. A structured content analysis of these websites was performed, with respect to; 1) LGBT-inclusive symbols; 2) Messaging directly addressing LGBT individuals; 3) Presence of a diversity/inclusion statement; 4) Explicit reference to LGBT individuals or sexual orientation in a diversity/inclusion statement; 5) Use of heteronormative imagery; and 6) Use of LGBT-inclusive imagery. Data was manually recorded and uploaded to an excel document for analysis. Results: None of websites featured LGBT-inclusive symbols or directly addressed LGBT individuals. 8% (n = 2) included a statement on diversity and inclusion, however only 4% (n = 1) explicitly referenced sexual orientation. In terms of visual content, 16% (n = 4) of websites included heteronormative photographs with none featuring LGBT-inclusive imagery. Conclusion: With the exception of one facility, none of the nursing homes acknowledged the sexual identity of residents with respect to inclusivity. None of the facilities examined were suggestive that they would be an inclusive environment for prospective LGBT residents. Greater effort is required to promote inclusivity of sexual minority individuals in the long term care setting.